Biomechanical analysis of ski jumping landing by means of wearable sensors - Bessone, V. (Technische Universität München, 2019)
Die Skisprunglandung spielt eine wichtige Rolle für Leistung und Sicherheit der Athleten. Wegen technologischer Probleme konzentrierten sich wenige Studien auf sie. Ziel der Dissertation war es, eine biomechanische Analyse der Landung mittels Inertialsensoren und Kraftmesssohlen durchzuführen. Die Ergebnisse deuten darauf hin, dass sich Athleten während der Landevorbereitung auf kinematische Parameter, wie den Skianstellwinkel fokussieren sollten, um auftretende Gelenkbelastungen zu reduzieren. Ski jumping landing plays an essential role in athletes` performance and safety. Despite its importance, few studies focused on landing, mainly due to technological problems. The aim of the thesis was to perform a biomechanical analysis of the landing, by means of inertial sensors and force insoles. The results indicate that, in order to reduce the impact force magnitude connected to the injuries, the athletes should focus on the kinematics before the landing, in particular, on the ski pitch.